2019
DOI: 10.1021/acs.molpharmaceut.8b01102
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Mechanism of Rosuvastatin-Induced Decrease in Mature hERG Protein Expression on Membrane

Abstract: The hERG potassium channel (IKr) encoded by human ether-a-go-go-related gene plays an important role in cardiac repolarization. Decreased IKr may lead to long QT syndrome, which subsequently causes torsade de pointes and sudden cardiac death. Previous studies have shown that statins inhibit IKr and are more potent in inhibiting hERG currents when combined with other drugs. Since chemical structure of rosuvastatin is similar to that of several IKr blockers (ibutilide and E-4031), the present study aimed to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…90 These changes can also affect the structures of integral membrane proteins which deform to maximize hydrophobic interactions with the surrounding lipid bilayer, 91 and other processes such as protein aggregation, 91 helix−helix interactions, 91 and the dimerization of membrane proteins. 92 We also note that statins can influence the structure and function of these proteins via other pathways (for example, statins can affect the folding of the human ether-a-go-go related genes (hERG) potassium channel by binding directly to the heat shock protein), 93 although this study is focused on simvastatin− membrane interactions, and the impact on the physical properties of the model bilayer.…”
Section: Discussionsupporting
confidence: 83%
“…90 These changes can also affect the structures of integral membrane proteins which deform to maximize hydrophobic interactions with the surrounding lipid bilayer, 91 and other processes such as protein aggregation, 91 helix−helix interactions, 91 and the dimerization of membrane proteins. 92 We also note that statins can influence the structure and function of these proteins via other pathways (for example, statins can affect the folding of the human ether-a-go-go related genes (hERG) potassium channel by binding directly to the heat shock protein), 93 although this study is focused on simvastatin− membrane interactions, and the impact on the physical properties of the model bilayer.…”
Section: Discussionsupporting
confidence: 83%
“…EPI was known to regulate activity of transcription factor SP1 (Feng et al. 2019 ). As indicated in Figure 6(A–D) , EPI could increase protein level of SP1 in both H9C2, CMs and CFs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that HIV protease inhibitors induce ERS in intestinal epithelial cells(Wuet al 2010) and ERS can down-regulate cardiac ion channel expression (Liu et al 2018). Referring to the effect of rosuvastatin on hERG (Feng et al 2019), ERS may play an important role in diLQTS. Whether hERG is affected by ERS requires further verification.…”
Section: Lopinavir/ritonavirmentioning
confidence: 95%
“…Many different structurally drug groups cause QT prolongation targeting hERG through disrupting the trafficking of protein (Dennis et al 2007, Nogawa and Kawai 2014. These drugs include arsenic (Ficker et al 2004), pentamidine (Kuryshev et al 2005), fluconazole (Han et al2011) and ketoconazole (Takemasa et al 2008), fluoxetine (Hancox and Mitcheson 2006), cardiac glycosides (Wang et al 2007), rosuvastatin (Feng et al 2019), thioridazine (Liu et al2020) and so on. Arsenic trioxide (As 2 O 3 ) is the first example of a drug that produces hERG liability by inhibition of channel protein trafficking through disrupting hERG-chaperone complexes (Ficker et al 2004).…”
Section: Disruption Of Herg Channel Traffickingmentioning
confidence: 99%